Collapsibility and Strength of Gypseous Soil Treated with Palm Fibers - Snodi, Lamyaa N.; Jassam, Mahmod G.; Hussein, Mazin A. (Engineering, Technology & Applied Science Research, 2025)
Collapsible soil is a type of soil that appears strong and stable in its dry state but loses stability when exposed to water, resulting in collapse. Such soil poses a major challenge in the field of geotechnical engineering. Gypseous soils are one type of collapsible soil; they are defined as soils containing a high percentage of gypsum (CaSO4.2H2O), which can make up a significant part of their mineral composition. These soils are found in arid and semi-arid regions, where the climatic conditions favor the gypsum formation due to the low rainfall and high evaporation rates caused by the high temperatures. Gypseous soils are highly soluble in water and have poor stability when used as a foundation for construction; therefore, they require special care and treatments to prevent building failures. In this study, the effect of adding palm fibers as an additive on the compressibility and strength of gypseous soil was examined. The soil used has a gypsum content of 56% and was collected from Tikrit City, Salah Aldeen Governorate, Iraq. Palm fibers were added to the soil at percentages of 0.1%, 0.3%, and 0.5% of the soil weight. Collapse and direct shear tests were conducted on both natural and treated samples. The results show a significant decrease in the Collapse Potential (CP) and a notable increase in the shear strength parameters, namely cohesion (c) and angle of internal friction (φ), for the treated soil. The improvement in CP reached 39.38% at 0.5% treatment. For the direct shear test, the increases in c and the angle of internal friction (φ) reached 52.78% and 18.57%, respectively, at 0.5% treatment.